Impact of the Surface Stress on the Volume and Freshwater Transport Through the Canadian Arctic Archipelago From a High‐Resolution Numerical Simulation. Issue 12 (13th December 2018) - Grivault, Nathan; Hu, Xianmin; Myers, Paul G.
Abstract: We use a numerical model forced with high temporal and spatial resolution atmospheric forcing to evaluate the volume and freshwater transport through the Canadian Arctic Archipelago (CAA). On average, the simulated inflow through the Queen Elizabeth Islands represents 40% of the transport entering the CAA through M'Clure Strait. The transport through Admunsden Gulf represents less than 10% of the total inflow. The impact of sea ice and winds on the volume and freshwater transports into and through this region is also investigated. At Nares Strait and West Lancaster Sound, the transport is overestimated due to too‐mobile sea ice but different physical processes related to surface stress. The ice is driving larger ocean flow in the first case, while causing less flow reduction in the second case. While the transport through the Queen Elizabeth Islands responds to the changes in surface stress over the Beaufort Gyre and northern Baffin Bay, local surface stress opposed to the mean flow over the straits tends to reduce the throughflow transport. In Parry Channel and the southern CAA, the surface stress tends to enhance the transport and have a greater impact locally. Finally, the surface stress related to sea ice motion can significantly change the transport in the CAA during the winter months. Plain Language Summary: We use a numerical computer model including high temporal and spatial resolution atmospheric forcing to evaluate the amount of water and freshwater flowing through the Canadian Arctic Archipelago (CAA). On average, we show that the inflow through the Queen Elizabeth Islands represents about slightly less (40%) than M'Clure Strait, which has historically been considered to be the main source of the inflow. We also show that the flow through the Amundsen Gulf is low (10% of the total), in agreement with previous studies. In addition, we demonstrate how the sea ice motion drives too much flow through West Lancaster Sound and Nares Strait and show the importance of the sea ice motion on the water and freshwater flows through key gates in and out of the CAA. This provides hints on how the dynamics of the flow through the CAA might change in the future with less sea ice cover in a warming world. The flux of freshwater through the CAA is potentially important as it may impact deep water formation in the Atlantic Ocean. Key Points: To correctly model transport through the CAA, ice velocity, and probably landfast ice, needs to be properly represented in numerical models Increasing surface stress reduces the flow through the Queen Elizabeth Islands but increases the flow through the central and southern CAA Freshwater transport is more sensitive to surface stress changes than volume transport